Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaa Manufaktur Yang Terdaftar di BEI Periode 2014-2016 - Adi Gunawan, I Made; Pituringsih, Endar; Widiastuty, Erna (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p27, 2019)
The purpose of this study is to analyze the factors that influence the value of manufacturing companies on the Indonesia Stock Exchange (IDX). The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2016 period as many as 146 companies. Sampling using purvosive sampling technique with several criteria to obtain a sample of 15 companies in a period of 3 years. Data analysis in this study using multiple linear regression. Based on the results of statistical data analysis both based on simultaneous tests (F-Statistic Test) and partial tests (t-Statistic Test), the results of research on dividend, liquidity, profitability, capital structure, and firm size are significant for firm value and have a positive direction . Keywords: Dividend policy, liquidity, profitability, capital structure, company size, firm value